Landscape of pediatric cancer treatment refusal and abandonment in the US: A qualitative study - Benedetti, Daniel J.; Hammack-Aviran, Catherine M.; Diehl, Carolyn; Beskow, Laura M. (Frontiers in Pediatrics, 2023)
Objective: To describe United States (US) pediatric oncologists’ experiences with treatment refusal or abandonment, exploring types and frequency of decision-making conflicts, and their impact. Study Design: We conducted exploratory qualitative interviews of pediatric oncologists (n=30) with experience caring for a pediatric patient who refused or abandoned curative treatment. Interviewees were recruited using convenience and nominated expert sampling, soliciting experiences from diverse geographic locations and institution sizes across the US. We analyzed transcripts using applied thematic analysis to identify and refine meaningful domains. Results: Many oncologists reported multiple experiences with refusal and abandonment. Most anticipated case frequency would increase due to misinformation, particularly on the internet. Interviewees described cases of treatment refusal and abandonment, but also a wider variety of cases than previously described in existing publications, including cases involving: non-adherence; negotiations for different treatments; negotiations for complementary and alternative medicine; delayed treatment initiation; and refusal of a component of recommended therapy. Cases often involved multiple stages or types of conflicts. Recurring patient/family behaviors emerged: clear opposition to treatment from the outset; hesitancy about treatment despite initiating therapy; and psychosocial circumstances becoming an obstacle to treatment completion. Oncologists revealed substantial professional and personal repercussions of these cases. Conclusions: Oncologist interviews highlight a broad range of conflicts, yielding a taxonomy of treatment refusal, non-adherence and abandonment (TRNA) that accounts for the heterogeneity of situations described. Cases’ complexity and interrelatedness points to a functional model of TRNA that includes families’ behaviors. This preliminary taxonomy and model warrant further research and examination to refine the model and generate strategies to prevent and mitigate TRNA.